Spatial Variation of the Radioactive Element Polonium-210 in a Coal Burning Power Plant Area of Malaysia - Alam, Lubna; Mazlin, Mokhtar; Islam, Mir Sujaul (Institute of Research and Journals (IRAJ), 2017)
This study presents the results of Po-210 analysis in water, total suspended solid and sediment samples collected from a coal burning power plant area of Malaysia. Hierarchical cluster analysis has been used to classify the sampling station based on the activity of Po-210. The calculation of flux allowed examining the vulnerability of study location based on the concentrations of Po-210. Among all the stations, ash pond is detected as the most vulnerable location and the less affected area is the inlet. Even though the fluxes of water and sediment are not so high, the coastal sea became the second most vulnerable station because of the higher Po-210 activity in TSS. As a whole, the study clearly indicates the impact of coal burning on the marine environment of Kapar coastal area of Malaysia.